An Examination of Economic Nationalism's Impact on India's Political Unrest Before and After Independence (International Journal of Innovative Research in Engineering & Management, 2021)
The economic condition before even the intrusion of foreign  invaders, India's economy was at its pinnacle, but following the  advent of the British, the country's financial situation  deteriorated, and after the entry of the Mughals and English, the  situation deteriorated even more. The sentiment of nationalism  has brought the Indian people together in such a manner that  they must have begun to worry about the country's resurrection,  particularly its economic situation. The purpose of this study is  to provide an overview of the Modern economic situation as  well as the impact of independence on it. Politics has a  significant influence on policy decisions and the  implementation of measures intended to improve the economy.  By focusing on policymaking for economic growth, this  research illustrates the financial situation in between  independence. The year 1991 was a pivotal year for changes,  Economy
Keywords: Economy; Finance; Government; Nationalism; Reforms